Sie sind auf Seite 1von 12

# ID : F-6-Integers 

Integers
For more such worksheets visit www.EduGain.com

(1)

(2)

(3)

(4)

(5)

A)

B)

A)

B)

A)

-30 = ______

B)

-37 = ______

C)

-97 = ______

D)

-66 = ______

E)

-90 = ______

F)

-77 = ______

A)

B)

C)

D)

E)

F)

A)

B)

## Choose correct answer(s) from given choice

(6)

An arithmetic sequence is a sequence of numbers a1, a2, a3,... where an - an-1 is the same value
for all n.
For example 2, 4, 6, 8, 10,....is such a sequence where the difference between adjoining numbers
is 2.
Given a, b, c, d and e are consecutive members of such a sequence, and that
a + b + c + d + e = 90, what is the value of c?

(7)

a. 15

b. 17

c. 20

d. 18

a. -(a - 14)

b. 14

c. a - 14

d. a

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

(8)
(9)

## Every integer to the left of zero on the number line have

value.

Simplify :
A)
B)

11 ( -2 ) + (-3551 / -53) + 6 18 =
(2544 / -53) - 18 ( -19 ) + ( -15 ) 18 =

## (10) Find the value of following :

A)
B)

( -4 ) ( -10 ) ( -2 ) 13 4 =
( -6 ) ( -3 ) ( -18 ) 8 =

## (11) Find how many integers are there between:

A)
C)
(12)

-1 and 0 =
-3 and 6 =

B)
D)

-2 and 7 =
-4 and 0 =

If a and b are two integers such that a is the predecessor of b, the value of a - b will be

Check True/False
(13) |a - b| = |a| - |b| where a and b are natural numbers and a > b
True
False
(14) Zero is not an integer.
True

False

True
False

## Many more such worksheets can be

generated at www.EduGain.com

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

(1)

A)

204
Step 1
The given expression can be expressed as:
114 + ( -25 ) + ( -12 ) - ( -134 ) - ( -6 ) - ( -41 ) - 54
= 114 -25 -12 + 134 + 6 + 41 - 54
= 204
Step 2
Therefore the value of expression 114 + ( -25 ) + ( -12 ) - ( -134 ) - ( -6 ) - ( -41 ) - 54 is
204.

B)

155
Step 1
The given expression can be expressed as:
( -16 ) + ( -45 ) - ( -57 ) - 17 - ( -176 )
= -16 -45 + 57 - 17 + 176
= 155
Step 2
Therefore the value of expression ( -16 ) + ( -45 ) - ( -57 ) - 17 - ( -176 ) is 155.

(2)

A)

80
Step 1
The given expression can be expressed as:
183 - ( -116 ) - 142 - ( -131 ) - 153 - 55
= 183 + 116 - 142 + 131 - 153 - 55
= 80
Step 2
Therefore the value of expression 183 - ( -116 ) - 142 - ( -131 ) - 153 - 55 is 80.

B)

389
Step 1
The given expression can be expressed as:
( -72 ) - ( -108 ) - ( -142 ) - ( -128 ) - ( -42 ) - ( -108 ) - 67
= -72 + 108 + 142 + 128 + 42 + 108 - 67
= 389
Step 2
Therefore the value of expression ( -72 ) - ( -108 ) - ( -142 ) - ( -128 ) - ( -42 ) - ( -108 ) 67 is 389.

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

(3)

A)

-31

B)

-98

Step 1

Step 1

Step 1

negative numbers

negative numbers

negative numbers

## and zero are integer,

accept fractions. we
can write all integers
in increasing order
as:
Integers = {..., -5, -4, 3, -2, -1, 0, 1, 2, 3, 4,
5, ... }

## and zero are integer,

accept fractions. we
can write all integers
in increasing order as:
Integers = {..., -5, -4, 3, -2, -1, 0, 1, 2, 3, 4,
5, ... }

## and zero are integer,

accept fractions. we
can write all integers
in increasing order as:
Integers = {..., -5, -4, 3, -2, -1, 0, 1, 2, 3, 4,
5, ... }

Step 2

Step 2

## The predecessor of 97 is = -97 - 1 = -98.

Step 2
The predecessor of 30 is = -30 - 1 = -31.
D)

C)

-38

-67

E)

F)

-91

-78

Step 1

Step 1

Step 1

## All positive numbers,

negative numbers
and zero are integer,

## All positive numbers,

negative numbers
and zero are integer,

## All positive numbers,

negative numbers
and zero are integer,

accept fractions. we
can write all integers
in increasing order
as:
Integers = {..., -5, -4, 3, -2, -1, 0, 1, 2, 3, 4,
5, ... }

accept fractions. we
can write all integers
in increasing order as:
Integers = {..., -5, -4, 3, -2, -1, 0, 1, 2, 3, 4,
5, ... }

accept fractions. we
can write all integers
in increasing order as:
Integers = {..., -5, -4, 3, -2, -1, 0, 1, 2, 3, 4,
5, ... }

Step 2

Step 2

The predecessor of -

The predecessor of -

90 is = -90 - 1 = -91.

77 is = -77 - 1 = -78.

Step 2
The predecessor of 66 is = -66 - 1 = -67.

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

(4)

A)

-60319

B)

D)

-164658

E)

A)

## Sum of -537 and 58890 = -537 + (58890) = -537 -58890

= -59427

-10151
Sum of -3439 and 6712 = -3439 + (6712) = -3439 -6712
= -10151

F)

-59427

## Sum of -93865 and 70793 = -93865 + (70793) = -93865 70793 = -164658

(5)

C)

-86923

-27226
Sum of -22303 and 4923 = -22303 + (4923) = -22303 -4923
= -27226

-12581
Step 1
The sum of 2448 and 2600
2448 + 2600 = 5048
Step 2
Now subtract 5048 from -7533
-7533 - 5048 = -12581
Step 3

B)

10557
Step 1
The sum of 90 and -4669
90 + (-4669) = 90 -4669 = -4579
Step 2
Now subtract (-4579) from 5978
5978 - (-4579) = 5978 + 4579 = 10557
Step 3

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

(6)

d. 18
Step 1
If you look at the question carefully, you will notice that a, b, c, d and e are consecutive
members and the difference between adjoining numbers is 2.
Therefore you can say that d = c + 2,
b = c - 2,
a=b-2
=c-2-2
= c - 4,
e=d+2
=c+2+2
=c+4
Step 2
According to question a + b + c + d + e = 90
By putting the value of a, b, d and e
(c - 4) + (c - 2) + (c) + (c + 2) + (c + 4) = 90
c - 4 + c - 2 + c + c + 2 + c + 4 = 90
c + c + c + c + c - 4 - 2 + 2 + 4 = 90
5c + 0 = 90
5c = 90
c=

90
5

c = 18
Step 3
Now you can say that the value of c is 18.
(7)

c. a - 14
Step 1
Since the value of 'a' is greater than 14, so that the value of a - 14 is positive.
Step 2
Therefore the absolute value of | a - 14 | is a - 14

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

(8)

negative
Step 1
Integers can be negative {-1, -2,-3, -4, -5, ... }, positive {1, 2, 3, 4, 5, ... }, or zero {0}.
The ordering of integer is given by:
... 3 < 2 < 1 < 0 < 1 < 2 < 3 < ...
An integer is positive if it is greater than zero and negative if it is less than zero.
Step 2
Therefore we can say that every integer to the left of zero on the number line have negative
value.

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

(9)

A)
Step 1
We can multiply/divide two numbers by the following steps:
1. First of all we have to multiply/divide sign of the numbers. we use negative sign
before the negative numbers and we can't use any sign before the positive numbers.
We can multiply sign as:
++=+
+-=--=+
We can divide sign as:
++=+
+-=--=+
2.Now we have to multiply/divide numbers.
for example 3 2 = 6,
3 (-2) = (-6),
(-3) 2 = (-6),
(-3) (-2) = 6.
and 4 2 = 2,
4 (-2) = (-2),
(-4) 2 = (-2),
(-4) (-2) = 2.
Step 2
Now 11 ( -2 ) + (-3551 / -53) + 6 18 can be simplified as:
11 ( -2 ) + (-3551 / -53) + 6 18
= (-22) + 67 + 108
=
B)
Step 1
We can multiply/divide two numbers by the following steps:
1. First of all we have to multiply/divide sign of the numbers. we use negative sign
before the negative numbers and we can't use any sign before the positive numbers.
We can multiply sign as:
++=+
+-=--=+
We can divide sign as:
++=+
+-=--=+
2.Now we have to multiply/divide numbers.
for example 3 2 = 6,

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

3 (-2) = (-6),
(-3) 2 = (-6),
(-3) (-2) = 6.
and 4 2 = 2,
4 (-2) = (-2),
(-4) 2 = (-2),
(-4) (-2) = 2.
Step 2
Now (2544 / -53) - 18 ( -19 ) + ( -15 ) 18 can be simplified as:
(2544 / -53) - 18 ( -19 ) + ( -15 ) 18
= (-48) - (-342) + (-270)
=

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

(10) A)

-4160
Step 1
We can multiply two numbers by the following steps:
1. First of all we have to multiply sign of the numbers. we use negative sign before the
negative numbers and we can't use any sign before the positive numbers.
We can multiply sign as:
++=+
+-=--=+
2. Now we have to multiply numbers.
for example 3 2 = 6,
3 (-2) = (-6),
(-3) 2 = (-6),
(-3) (-2) = 6.
Step 2
To solve ( -4 ) ( -10 ) ( -2 ) 13 4, first of all we have to multiply first two numbers
after that we have to multiply result with the next number and so on as shown below:
( -4 ) ( -10 ) ( -2 ) 13 4
= 40 ( -2 ) 13 4
= -80 13 4
= -1040 4
= -4160
Step 3
Therefore the value of ( -4 ) ( -10 ) ( -2 ) 13 4 is -4160.

B)

-2592
Step 1
We can multiply two numbers by the following steps:
1. First of all we have to multiply sign of the numbers. we use negative sign before the
negative numbers and we can't use any sign before the positive numbers.
We can multiply sign as:
++=+
+-=--=+
2. Now we have to multiply numbers.
for example 3 2 = 6,
3 (-2) = (-6),
(-3) 2 = (-6),
(-3) (-2) = 6.
Step 2
To solve ( -6 ) ( -3 ) ( -18 ) 8, first of all we have to multiply first two numbers after
that we have to multiply result with the next number and so on as shown below:

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

( -6 ) ( -3 ) ( -18 ) 8
= 18 ( -18 ) 8
= -324 8
= -2592
Step 3
Therefore the value of ( -6 ) ( -3 ) ( -18 ) 8 is -2592.

(11) A)

B)

Step 1

Step 1

## All positive numbers, negative

numbers and zero are integer, accept
fractions. we can write all integers as:
Integers = {..., -5, -4, -3, -2, -1, 0, 1, 2,

## All positive numbers, negative

numbers and zero are integer, accept
fractions. we can write all integers as:
Integers = {..., -5, -4, -3, -2, -1, 0, 1, 2,

3, 4, 5, ... }

3, 4, 5, ... }

Step 2

Step 2

## Now the all integers between -1 and 0

can be written as: { 0 }.

## Now the all integers between -2 and 7

can be written as: { -1, 0, 1, 2, 3, 4, 5,
6 }.

Step 3

Step 3

## Therefore we can say that the integers

between -1 and 0 = 0.

C)

## Therefore we can say that the integers

between -2 and 7 = 8.
D)

Step 1

Step 1

## All positive numbers, negative

numbers and zero are integer, accept
fractions. we can write all integers as:
Integers = {..., -5, -4, -3, -2, -1, 0, 1, 2,
3, 4, 5, ... }

## All positive numbers, negative

numbers and zero are integer, accept
fractions. we can write all integers as:
Integers = {..., -5, -4, -3, -2, -1, 0, 1, 2,
3, 4, 5, ... }

Step 2

Step 2

## Now the all integers between -3 and 6

can be written as: { -2, -1, 0, 1, 2, 3, 4,
5 }.

## Now the all integers between -4 and 0

can be written as: { -3, -2, -1 }.

Step 3
Therefore we can say that the integers
between -3 and 6 = 8.

## (C) 2015 EduGain (www.EduGain.com)

Step 3
Therefore we can say that the integers
between -4 and 0 = 3.

## Personal use only, commercial use is strictly prohibitated

ID : F-6-Integers 

(12)

-1
Step 1
Because a is predecessor of b therefore the value of a = b - 1
Step 2
The value of a - b = b - 1 - b
=b-b-1
= -1

(13) True
Step 1
Because a and b are natural numbers and a > b therefore the value of |a - b| and |a| - |b| is
always positive.
Therefore |a - b| = |a| - |b|
Step 2
(14) False
Step 1
Integers can be negative {-1, -2,-3, -4, -5, ... }, positive {1, 2, 3, 4, 5, ... }, or zero {0}, So we
can say that Zero is an integer.
Step 2